Analysis of Factors Affecting the Number of International Migrations in Java - Salsa Billah, Juana Rizqi; Shofwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Java Island is a major contributor to the number of international labor migration in Indonesia which continues to increase every year. This is driven by various social and economic factors that have become important issues in terms of global development. This study aims to analyze the economic and social factors namely poverty, minimum wage, divorce and average years of schooling in influencing the number of international labor migration in Java Island in 2018-2023. This research uses a quantitative approach by processing secondary data in the form of panel data with cross section data of 6 provinces in Java Island and the range of 2018 to 2023. Panel data regression analysis is used to see the relationship between the dependent variable and the independent variable. The results showed that the poverty variable had a negative and significant effect, while the minimum wage variable had a positive and insignificant effect on the number of international labor migration in Java Island in 2018-2023. While the divorce variable has a positive and significant effect, and the average length of schooling variable has a negative and significant effect on the number of labor international migration in Java Island in 2018-2023.